Low-noise single-photon detector for the 1.5-mu m wavelength region - Lee, Seoung Hun; Jeong, Kyu Hyeon; Kim, Kyong Hon; Lee, Min Hee; Ahn, Joon Tae; Choi, Sang Hyun; Park, Chul-Woo; Park, Jun-Bum; Moon, Sung (KOREAN PHYSICAL SOC, 2007)
This paper describes an experimental demonstration and characterization of a InGaAs avalanche-photodiode (APD)-based low-noise single-photon detector developed for quantum cryptography at a wavelength of 1.5 mu m. At the operation temperature of -50 degrees C with a gated Geiger mode, we obtained a quantum efficiency of 21 % with a dark count probability per gate of 2.6 x 10(-5) for a gate frequency of 10 kHz. The measured noise equivalent power (NEP) was 8.6 x 10(-17) W/Hz(1/2), which was the lowest value achieved so far at a thermoelectrically cooled temperature, which is an important factor for low quantum-bit error rates (QBER) in a quantum key distribution (QKD). The afterpulsing probability measured by varying the gate duration and separation indicated that the gate separation should be greater than 40 mu s for 2.4-ns gate pulses to avoid the afterpulse effect. The developed single-photon detector turns out to be suitable for a 73-km fiber-optic quantum-key distribution in realistic conditions.
Keywords: QUANTUM KEY DISTRIBUTION; 1550 NM; CRYPTOGRAPHY; PERFORMANCE; PLUG